2015
DOI: 10.1212/wnl.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Urologic and gastrointestinal symptoms in the dystroglycanopathies

Abstract: Objective: To determine the frequency of urologic and gastrointestinal (GI) symptoms in a cohort of individuals with dystroglycanopathy compared with healthy household controls.Methods: Participants in a North American dystroglycanopathy natural history study (NCT00313677) and other members of their households completed a questionnaire modified from validated instruments and clinical criteria. Urologic and GI symptom frequency, effect on patient life, and medications taken for these symptoms were assessed. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…The expression of dystrophin in smooth muscle cells of human and rat bladder tissue observed here is in line with previous research showing dystrophin expression in smooth muscle cells of healthy human bladder tissue. 9 The prostate pathology in the human tissue sample used could result in morphological changes of the bladder (decreased neuronal density, increased epithelial turnover, increased fibrosis in the submucosal layer). 19 This is why we chose not to quantitate dystrophin expression in these samples but only to verify whether dystrophin was present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of dystrophin in smooth muscle cells of human and rat bladder tissue observed here is in line with previous research showing dystrophin expression in smooth muscle cells of healthy human bladder tissue. 9 The prostate pathology in the human tissue sample used could result in morphological changes of the bladder (decreased neuronal density, increased epithelial turnover, increased fibrosis in the submucosal layer). 19 This is why we chose not to quantitate dystrophin expression in these samples but only to verify whether dystrophin was present.…”
Section: Discussionmentioning
confidence: 99%
“…Dystrophin is not expressed exclusively in striated muscle but also in other tissues (i.e., brain, retina, kidney) . Recently, dystrophin was found in smooth muscle cells of normal human bladder tissue …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Affected individuals report symptoms of both bladder and bowel dysfunction. The most common bowel complaint is constipation, which in X-linked Duchenne Muscular Dystrophy (DMD) can become life-threatening, but generally the most disabling is fecal incontinence [30,31]. One series reported that in 47% of boys with DMD undergoing a colonic transit test, the radiopaque markers were retained in the recto-sigmoid, suggesting functional pelvic outlet obstruction [30].…”
Section: Muscular Dystrophies and Mitochondrial Disordersmentioning
confidence: 99%
“…Loss of the alpha-dystroglycan-laminin interaction, due to defective glycosylation of alpha-dystroglycan, underlies a group of congenital muscular dystrophies often associated with brain malformations, referred to as dystroglycanopathies, where NBD is reported [31]. Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is frequently associated with chronic intestinal pseudo-obstruction.…”
Section: Muscular Dystrophies and Mitochondrial Disordersmentioning
confidence: 99%